ROAD GEOMETRIC REDESIGN USED AUTOCAD®2D: A CASE JALAN SILIWANGI MAJALENGKA, INDONESIA - Ega Purnama; Amanatullah Savitri; Adinda Fajarika (LEADER: Civil Engineering and Architecture Journal, 2024)
Jalan Siliwangi is a road located in Panyingkiran that is a link to the city. This design planning starts in the Kadipaten sub-district and extends to the Panyingkiran sub-district is called jl. Siliwangi is 5.3 kilometers long. In addition, the design standard criteria in this study refer to the road geometric guidelines issued by the Ministry of Public Works and Public Housing Circular Letter of 2020 of the Director General of Highways. The results of the geometric design visualized in the form of drawings using AutoCAD 2D. The design speed (Vd) set at 60 km/h with a horizontal arc radius of 358 m, a maximum slope of 4%, and an elevation (e max) of 8%. Based on these design criteria, a spiral curve with a circular arc length (Lc) of 74,996 m obtained. Then, the calculation results of the long vertical alignment of the PPV (L) of one type of concave curve are calculated.